Changes in the External Secutiry Environment, Future Trends, Potential Risks and Challenges - Dovchin, Myagmar (Mongolian Journal of Strategic Studies, 2025)
No abstract in English Аюулгүй байдлын гадаад орчны өөрчлөлт, цаашдын хандлага, учирч болзошгүй эрсдэл, сорилт